Surgical-aware video masked autoencoders with phase-conditioned attention for laparoscopic action recognition - Hakim Nasaoui; Hassan Silkan; Insaf Bellamine (Universitas Ahmad Dahlan, 2026)
Fine-grained surgical action recognition in laparoscopic videos remains a challenge, even with recent advances in deep learning. While current VideoMAE approaches reach 89.11% accuracy on cholecystectomy tasks, they face specific limitations. Random masking strategies often miss surgical instruments that occupy only 10% to 15% of frames. Furthermore, context-independent models struggle with visually similar actions across different phases, and symmetric two-stream architectures tend to waste computational resources. To solve this, we developed SA-VideoMAE, a surgical-aware video masked autoencoder specifically designed for laparoscopic action recognition. Our method utilizes surgical-aware adaptive masking that integrates YOLOv7x object detection to prioritize instrument patches. This increased instrument visibility from 10% to 60% during training, ensuring the model focuses on action-relevant regions rather than static backgrounds. We also utilized phase-conditioned hierarchical attention to inject learnable phase embeddings into the attention mechanisms, enabling the model to disambiguate visually similar actions based on surgical context. For efficiency, our asymmetric dual-stream architecture processes RGB using ViT-Base (86M parameters) and optical flow using ViT-Tiny (5.7M parameters), achieving a 47% parameter reduction compared to symmetric designs. Our training process then balanced reconstruction, classification, temporal consistency, and phase prediction through a novel multi-objective optimization strategy. Results from Cholec80's Calot's Triangle Dissection phase show 93.5% accuracy, representing a 4.4 percentage-point improvement over the verified baseline. Notably, challenging action recall improved from 51% to 74% while maintaining real-time inference at 62ms per clip. These findings demonstrate that encoding surgical domain knowledge into video architectures significantly enhances action recognition performance.